2014
DOI: 10.5194/acp-14-4369-2014
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol variability and atmospheric transport in the Himalayan region from CALIOP 2007–2010 observations

Abstract: Abstract. This work quantifies the spatial distribution of different aerosol types, their seasonal variability and sources.The analysis of four years of CALIOP (CloudAerosol LIdar with Orthogonal Polarization) vertically resolved aerosol data allows the identification of spatial patterns of desert dust and carbonaceous particles in different atmospheric layers. Clusters of Lagrangian back trajectories highlight the transport pathways from source regions during the dusty spring season. The analysis shows a prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Hamburger et al [2013] found evidence that biomass burning aerosols emitted in Venezuela are transported by the easterly trade winds toward the Andes and then orographically lifted into the FT. Similar indications of natural and anthropogenic species lifted along high mountains have been found for the Himalayan region [Bucci et al, 2014;Cong et al, 2015] and the Swiss Alps [Griffiths et al, 2014].…”
Section: Introductionsupporting
confidence: 57%
“…Hamburger et al [2013] found evidence that biomass burning aerosols emitted in Venezuela are transported by the easterly trade winds toward the Andes and then orographically lifted into the FT. Similar indications of natural and anthropogenic species lifted along high mountains have been found for the Himalayan region [Bucci et al, 2014;Cong et al, 2015] and the Swiss Alps [Griffiths et al, 2014].…”
Section: Introductionsupporting
confidence: 57%
“…The slightly lower DecemberJanuary values were attributed to the confinement of the IGP polluted boundary layer below the site's altitude. Furthermore, synoptic-scale transport and changing air-mass origin affect the aerosol loading over the Himalayan sites (Xu et al, 2014;Bucci et al, 2014). The annual variation of the σ ap seems to follow that of the BC mass fraction, which was found to be ∼ 1 % during the monsoon and 7.6 % during winter associated with variation in σ ap (at 0.678 µm) from 0.9 to 33.9 Mm −1 .…”
Section: Diurnal Cycle Of Aerosol Propertiesmentioning
confidence: 91%
“…To make such operational systems robust, there is a need to evaluate and refine fire-aerosol relationships in multiple regions. Specific to Asia, most of the biomass burning aerosols are often mixed from fossil fuel combustion and dust emissions (Kaskaoutis et al 2009, Bucci et al 2014, Mishra et al 2014. In such a context, an important question to address is 'how much of the AOD increase is due to biomass burning and how well do satellite fire retrievals explain AOD variation?…”
Section: Introductionmentioning
confidence: 99%